Molecular Docking Study of Boheco Desire (An Ayurvedic Proprietary Medicine) (International Journal of Ayurveda and Pharma Research, 2024)
BOHECO DESIRE is an Ayurvedic proprietary medicine formulated in capsule form, recommended for enhancing sexual health, libido, stamina, and energy. Objectives: This study aims to explore the molecular binding interactions of the major phytocompounds present in BOHECO DESIRE with a target protein and also to understand binding affinity and bioavailability, using advanced computational tools. Methodology: Molecular docking studies were performed using ChemDraw 20.1.1. Glide extra precision (XP) scoring tools were employed to calculate the docking scores. The binding energy of the receptor-phytoconstituent complexes was calculated using the Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) method. Additionally, the QikProp module from Schrödinger was used to predict the ADME (Absorption, Distribution, Metabolism, Excretion) and physicochemical properties of the phytoconstituents. Results: Docking scores for L-DOPA, Cannabidiol, and Delta-9 Tetrahydrocannabinol suggest strong binding affinity with the target protein 1XOJ, with scores ranging from -9.4 to -4.1 kcal/mol. The van der Waals energy (Glide evdw) between -42.5 and -24.11 kcal/mol indicates favorable ligand-protein interactions. Glide energy, which includes van der Waals, electrostatic, and solvation energies, ranged from -45.07 to -26.53 kcal/mol, reinforcing the potential for stable complexes. Binding free energy values (-76.6 to -35.73 kcal/mol) suggest energetically favorable interactions. ADME predictions showed high oral absorption for Withanolide A, Delta-9 THC, and Cannabidiol, with the highest Caco-2 permeability for Delta-9 THC. Conclusion: The phytoconstituents demonstrated a strong binding affinity with 1XOJ with favorable ADME profiles. This indicates that BOHECO DESIRE's phytocompounds may have beneficial effects in sexual health.